Evaluasi dan Rekomendasi Perbaikan Information Architecture pada Website menggunakan Human-Centered Design (HCD) (Studi pada: Program Studi Pendidikan IPS ULM Banjarmasin) - Aprivisi Ewa Abbas; Retno Indah Rokhmawati; Diah Priharsari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Social Studies Education (PIPS) ULM Banjarmasin is one of the study programs under the auspices of the Faculty of Teacher Training and Education (FKIP) ULM Banjarmasin. PIPS ULM Banjarmasin uses the website as a media delivery information. However, there are still problems found on the website based on the author's observation and interview that conducted to the users and stakeholders of the website such as unfamiliar category naming, grouping content that does not conform to its category, less-updated content and the uninteractive user interface of the website. Based on the problems found, those problems are categorized in the field of website's Information Architecture. To overcome those problems, evaluation and recommendation of solution design are needed. This research uses the Human-Centered Design (HCD) approach to produce an interactive design solution. Card sorting is used to help the compilation of the information content on the solution design based on user needs with the end result of Sitemap. In designing the solution design, guidelines are used to limit the scope of the problems so the problems that had been defined can be focused to be solved. The guidelines which are used came from usability guidelines, the supporting website and the consent of the stakeholders. Once the design of the solution is completed, the increased value of the aspect is achieved. The initial value of success rate aspect was 31.11% and has increased to 91.11%. The initial value of directness aspect was 14.45% and has increased to 60%. The initial value of time spent aspect was 44.37 s and has reduced to 13.49 s. The initial value of first click aspect was 21.11% and has increased to 76.67%. The initial value of destination aspect was 31.11% and has increased to 91.11%.